Modeling of the tension stiffening behavior and the water permeability change of steel bar reinforcing concrete using mesoscopic and macroscopic hydro-mechanical lattice model. (12th July 2021) - Bui, T.S.; Pham, D.T.; Vu, M.N.; Nguyen, T.N.; Nguyen-Sy, T.; Nguyen, V.P.; Nguyen-Thoi, T.
Highlights: Macro-mesoscopic HM lattice models for a tensioned reinforced NSC member. Tension stiffening behaviour and water permeability change are well described. Permeability change corresponds to microcracks' initiation, growth and coalescence. Effect of aggregate volume fraction is investigated. Abstract: Mesoscopic and macroscopic hydromechanical lattice simulations are performed for studying the tension stiffening behavior, the change in permeability, and their linking of a tensioned reinforced normal strength concrete (NSC) member. In the lattice framework, the hydromechanical coupling is carried out by dual Delaunay triangles and Voronoi polygons, where transport elements are placed along the edges of the Voronoi polygons while mechanical elements are edges of Delaunay triangles. At the mesoscale, concrete is considered as a constitution of three phases: aggregate, cement paste and interfacial transition zones (ITZ). Two mesoscopic components cement paste and ITZ, as well as the concrete at the macroscale, are modeled by a damage model including softening strain feature. The crack opening is linked to the damage variable. Fluid flow obeys Darcy's law in the intact conduit element and Poiseuille's law in the crack. Validation against experimental results available in the open literature for NSC tie specimens shows that both current macroscopic and mesoscopic lattice hydromechanical models are appropriated to describe the tensile stiffening and damage induced permeability of NSC reinforced by a steel bar. Mesoscopic modeling helps to get insights of the aggregate volume fraction effect.